IDENTIFIKASI MORFOLOGI TANAMAN AREN ASAL KABUPATEN LEBAK - Nurmayulis Nurmayulis; Susiyanti Susiyanti; Sulastri Isminingsih; Reza Maulana Muhammad; Saiful Saiful; Septi Yulianti; Rizky Puspita Sari (Jurusan Agroekoteknologi Fakultas Pertanian Untirta, 2021)
Sugar palm is a commodity that has the potential to be developed. Sugar palm is developed to produce various products and raw materials for derivative products. Currently, there is a lot of morphological diversity of sugar palm plants found in the field. Presently, identification of various types of sugar palm morphologically in Banten Province is still limited. Sugar palm in Banten Province is found in various locations, such as in Lebak. This study aimed to determine the characteristics of Aren seedlings originating from Lebak Regency. The hypothesis in this study is that there are several characteristics of palm seedlings originating from Lebak Regency. This research was conducted in August 2019 - November 2019 located in Green House, Cinanggung Village, Serang City, Banten Province. This study uses a descriptive method, through a quantitative approach with data analysis and interpretation, and conclusion. The observation parameters in this study were: Plant Height (cm); Number of leaves per plant (strands); Leaf width (cm); Leaf length (cm); stem diameter (cm); Leaf color. The results showed that Aren from Lebak Regency aged 1 year have an average plant height of 28.1 cm, a pinnate leaf shape and a thick like a palm leaf, with an average number of 1 leaves, an average leaf length of 16.4 cm, and an average leaf width of 6.8 cm, with dark green leaf color. The stem diameter has a strength correlation with plant growth level like as plant height, the higher the plant. The greater the stem diameter obtained in this study is 2.19 cm.